KOMPATIBILITAS ISLAM DAN DEMOKRASI: TELAAH ATAS PANDANGAN HIZBUT TAHRIR INDONESIA (HTI) TERHADAP ISLAM DAN DEMOKRASI - ANA SABHANA AZMY (Jurnal Dialog, 2017)
Fundamentalist Islamic groups are often identified as resistant groups towards revolutionary values coming from the West. In Indonesian context, fundamentalist groups was represented by, one of them, Hizbut Tahrir Indonesia (HTI). Fundamentally, HTI as a group opposes any changes and supports the establishment of Islamic nation. From this perspective, HTI is against democracy as a product of western thought. In fact, HTI is struggling for the unity Islamic ummah under khilafah islamiyyah by khalifah as a leader. From this background this paper aims at answering to questions. First, how is HTI view as a fundamentalist group on the compatibility of Islam to democracy? Second, Is Islam compatible with democracy? KEY WORDS: HTI, Democracy, Compatibility, Islam